Comparative study of Saudi and Turkish coffee consumption in Saudi Arabia: insights into sociodemographic factors and caffeine intake - Bawazeer, Nahla Mohammed; Binsunaid, Faisal; Alraqea, Atheer; Al Fayez, Mazen M.; Alhumaidan, Omar; Fallata, Ghadir; Aldahash, Rehab; Benajiba, Nada (Frontiers in Nutrition, 2024)
Background Saudi and Turkish coffee consumption in Saudi Arabia is increasing considerably, and the nationwide consumption patterns need elucidation to determine the contributions of Saudi and Turkish coffee toward nutrition and health. Aim To describe the frequency and quantity of Saudi and Turkish coffee consumption and assess their association with sociodemographic factors. Methods This cross-sectional study included 1,030 participants (Saudi Arabia) recruited via an online questionnaire study that collected information on general characteristics and coffee consumption. The caffeine content in Saudi and Turkish coffees was quantified using a standard laboratory technique. The total caffeine intake and exposure were calculated. Associations between the different parameters were assessed. Results Significant differences were observed in several demographic and sociodemographic factors according to the frequency of coffee intake. Specifically, individuals who consumed Saudi coffee almost every day (approximately 40% of respondents) were more likely to differ in age, body mass index, marital status, work status, monthly income, and region compared to those who consumed it less frequently. Additionally, one-third of the respondents consumed Turkish coffee, and the frequency of its consumption showed significant differences according to age, nationality, marital status, educational level, and region. Notably, the highest caffeine exposures were 0.95 mg/kg/d for Saudi coffee, 1.31 mg/kg/d for Turkish coffee, and 2.07 mg/kg/d for both coffees combined. The mean contribution to the 400 mg daily caffeine intake limit was significantly higher for Saudi coffee compared to Turkish coffee (p < 0.05). Conclusion Saudi and Turkish coffee consumption patterns vary across sociodemographic characteristics, where Saudi coffee is generally more consumed. Our study may form a basis for nutrient education in terms of coffee consumption to promote a healthy lifestyle.